PENGARUH RASIO PROFITABILITAS DAN RASIO AKTIVITAS TERHADAP PERTUMBUHAN LABA PADA PT GUDANG GARAM TBK PERIODE TAHUN 2013-2022 - Handini, Hani; Surahman, Arif (Jurnal Nusa Manajemen, 2024)
This research aims to determine the effect of the Profitability Ratio proxied by Net Profit Margin and the Activity Ratio proxied by Total Asset Turnover on PT Gudang Garam Tbk's Profit Growth, both partially and simultaneously. The population chosen was the financial report of PT Gudang Garam Tbk, with the sample used being the financial position report and profit and loss report for the 2013-2022 period. This research uses a quantitative approach and documentation data collection techniques. The analytical methods used are Multiple Linear Regression Analysis. Based on partial research results using the t test, it was concluded that Net Profit Margin had a significant effect on Profit Growth with a significance value of 0.001 < 0.05. Meanwhile, Total Asset Turnover has no significant effect on Profit Growth with a significance value of 0.413 > 0.05. Simultaneous test results (F test) show that Net Profit Margin and Total Asset Turnover together have a significant effect on Profit Growth with a significance value of 0.001 < 0.05 with an F_count value of 21.160 > F_table 4.74.